Kesesuaian Implementasi Pembelajaran MIPA dengan Tahap Perkembangan Kognitif Piaget - Rayimas Priti Aisyapuri; Hafizhah Khairana; Dela Amelia Damayanti; Reni Reni; Ikmawati Ikmawati; Kurniawan Kurniawan (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study explores the alignment between science learning practices and children’s cognitive development stages based on Jean Piaget’s theory. Ten academic publications were systematically reviewed to examine how Piaget’s framework can be applied in science education. The findings highlight that integrating cognitive development theory is highly relevant for improving the quality of teaching and learning in schools. At the concrete operational stage (approximately 7–11 years), children learn best through direct experiences, manipulation of real objects, contextual media, and experiments that connect concepts with daily life. These methods help foster curiosity and reinforce conceptual understanding. As learners progress to the formal operational stage (around 11 years and above), they begin to think abstractly, reason logically, and analyze critically. At this level, student-centered approaches, inquiry-based methods, and constructivist learning become more effective in enhancing problem-solving, creativity, and higher-order thinking skills. The review also indicates that adapting instruction to developmental stages supports more meaningful and sustainable learning outcomes. In the Indonesian educational context, this approach can address challenges such as limited classroom facilities, diverse student learning styles, and a curriculum that is often overloaded. By applying Piaget’s insights, teachers can design learning strategies that bridge abstract concepts with concrete understanding, thus increasing student motivation and engagement. In conclusion, aligning science education with Piaget’s cognitive stages is an effective way to improve student performance and ensure long-term academic growth. The study provides valuable input for teachers, researchers, and policymakers in developing innovative, student-centered science and mathematics education.